Physico-chemical and functional properties of microfluidized egg yolk. (April 2021) - Suhag, Rajat; Dhiman, Atul; Thakur, Dhruv; Kumar, Anit; Upadhyay, Ashutosh
Abstract: The present research investigated the effect of microfluidization treatment (103, 138, 172, and 207 MPa) on pH, refractive index (RI), color measurements, rheology, particle size, emulsifying properties, and thermal denaturation of egg yolk. Color parameters were significantly (p < 0.05) effected by microfluidization treatment. Rheological measurements showed the conversion of newtonian nature to the shear-thinning nature of egg yolk upon microfluidization treatment. Further, yield stress ( τ o ), consistency constant (K), and flow behaviour index (n) were affected by microfluidization. Microfluidization caused a reduction in particle size of yolk with an increase in pressure up to 172 MPa and particle size increased at 207 MPa. Emulsifying activity index (EAI) increased from 30.49 m 2 /g (control) to 32.41 m 2 /g (MEY2) but decreased as microfluidization pressure was increased. Emulsifying stability index (ESI) increased at 103 MPa but decreased as microfluidization pressure increased further. Thermal analysis revealed increase in denaturation temperature as microfluidization pressure increased. Highlights: Shear thinning behaviour of egg yolk post microfluidization treatment. Microfluidization reduced the particle size of egg yolk and improved the physicochemical and functional properties. Microfluidization treatment at 138 and 103 MPa improved the EAI and ESI, respectively. Microfluidization increased the denaturation temperature of egg yolk proteins. Thereby explaining suitability for further food processing.